(untitled) (Journal of Medical & Health Sciences Review, 2026)
Background: Dermatofibrosarcoma protuberans (DFSP) is a rare, low-grade cutaneous soft tissue sarcoma with locally aggressive behavior and a marked tendency for local recurrence if incompletely excised. Presentation in the breast region is uncommon and can mimic benign breast or skin lesions, leading to delayed diagnosis. Case Presentation: A 65-year-old woman presented with a slowly enlarging swelling over the left breast for approximately five years, associated with intermittent mild pain and pruritus. On initial assessment, a firm, mobile, non-tender mass measuring about 6 × 8 cm was noted in the upper outer quadrant, with prominent superficial veins and mild protuberant nodularity. The patient re-presented one year later with progression to 10 × 9.5 cm and a 5 cm “budding” protuberant component with overlying erythema. Incisional biopsy revealed a spindle-cell neoplasm arranged in a storiform pattern with low mitotic activity (3–4/10 HPF) and no necrosis. Immunohistochemistry showed strong diffuse CD34 positivity, low Ki-67 proliferative index (<5%), and negativity for desmin, ASMA, and cytokeratin (AE1/AE3), confirming DFSP. The patient underwent wide local excision, and postoperative recovery was uneventful. She was counseled for regular follow-up due to the risk of local recurrence. Conclusion: DFSP should be considered in persistent, slow-growing breast or chest wall masses, particularly when a protuberant component develops. Early biopsy and complete surgical excision with adequate margin assessment are essential for optimal local control.